Customer perception towards service quality provided by Tabung Haji Seremban / Zuhairah Hasan and Ridhawati Hj. Zakaria - Hasan, Zuhairah; Zakaria, Ridhawati (Research Management Institute (RMI), 2009)
Tabung Haji (TH) birth from the idea of working paper presented by the Royal Professor Ungku Aziz titled, “Plan to Improve the Economy of Prospective Pilgrims” in 1959. The functions of this organization are to enable Muslims to save gradually to support their expenditure during pilgrimage and for other beneficial purposes, to enable Muslims to have active and effective participations in investment activities permissible in Islam through their savings and to protect, safeguard interests and ensures welfare of pilgrims during pilgrimage by providing various facilities and services. The purpose of this research is to study the customer perceptions towards the service quality provided by Tabung Haji Seremban. The research used the service quality (SERVQUAL) dimensions. There are 5 dimensions in SERVQUAL which are reliability, responsiveness, assurance, empathy and tangible. This dimension will be used to identify customer perception towards service quality provided by Tabung Haji Seremban as quality services depend on the Tabung Haji Seremban employee’s performance and their ability to provide the services. In this study, the methods used are questionnaire to identify the relevant information regarding the study on customer perception towards service quality provided by Tabung Haji Seremban. 100 questionnaires were given to respondents to answer the questionnaire. The result on customer perception towards service quality will suggest whether the Tabung Haji Seremban may need changes or improvement in their service performance in order to be able to provide continuously quality services and achieve their motto and quality policy.